Thirty‐day recurrence after ischemic stroke or TIA. Issue 10 (17th September 2018) - Khanevski, Andrej Netland; Bjerkreim, Anna Therese; Novotny, Vojtech; Næss, Halvor; Thomassen, Lars; Logallo, Nicola; Kvistad, Christopher E.
Abstract: Background: Incidence of recurrent stroke is highest within 30 days after the initial ischemic stroke (IS) or TIA, but knowledge about early recurrence is lacking. We aimed to identify etiological groups with highest risk of early recurrence and assess how the TOAST classification identified index stroke etiology. Methods: Medical records of 1874 IS and TIA patients in the Bergen NORSTROKE registry were retrospectively reviewed for identification of recurrent IS or TIA within 30 days after index IS or TIA. Stroke etiology was determined by review of electronical medical journals. Logistic regression was used to calculate odds ratios (OR) for 30‐day recurrence. Results: Thirty‐three patients (1.8%) were readmitted with recurrent IS or TIA within 30 days after index stroke. By using TOAST, 12 patients were initially classified with stroke of unknown etiology (SUE). Etiologies behind recurrent IS or TIA were after the recurrent episode identified as extracranial large artery atherosclerosis (LAA) in 14 patients (42.4%), intracranial arterial pathology in seven patients (21.2%), active malignancy in six patients (18.2%), and cardio embolism in four patients (12.1%). Small vessel occlusion and SUE were the causes in one patient each. Logistic regression showed that patients with stroke of other determined etiology (SOE) and LAA had increased risk of 30‐day recurrence (OR = 9.72, 95% CI 1.84–51.3, p < 0.01 and OR = 4.36, 95% CI 2.01–9.47, p < 0.01, respectively). Conclusion: Patients with LAA and SOE had increased risk of recurrent IS or TIA within 30 days. TOAST was inadequate at identifying exact etiologies behind recurrent stroke at index event. Abstract : Early recurrent stroke poses a threat to stroke patients, but causes behind early recurrence are not well studied. We found that patients with large artery atherosclerosis, intracranial pathology, and active cancer were at highest risk for recurrence within 30 days. An accurate determination of etiology of first stroke is important for selection of appropriate secondary prophylaxis and prevention of early recurrence.